Komodifikasi Pengarah Acara Di Era Peralatan Digital: Studi Kasus Liputan 6 Surya Citra Televisi - Zakaria Satrio Darmawan (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2019)
This research attempts to explain the commodification of workers of a program director in the mass media industry, a case study on Liputan 6 SCTV. The researcher applies the concept of Media Political Economy theory, which is the focus of the research of workers' commodification. This research uses a critical paradigm with a qualitative approach and case study methods. This research revealed that SCTV Television Media continues to develop business and innovation to adapt to the development of the media and technology industry, including the application of digital equipment. In doing so, there is a commodification of workers in the coverage of SCTV 6 through the addition of workload and responsibilities or the provision of dual tasks and low wages. The forms of commodification that occur are body exploitation, economic exploitation, and ability exploitation. The Program Director accepts exploitation as natural for his profession because of the benefit principle process. With limited human resources utilized to be able to maximize the ability to be able to complete two or more jobs at one time with the reward not directly proportional to the workload provided.